PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS SCIENTIFIC APPROACH BERBANTUAN VIRTUAL LABORATORY UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA - Dya Ayu Cahya Timur; Yushardi Yushardi; Bambang Supriyadi (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract This research was a development research to produce development products in the form of worksheets based on a scientific approach assisted by a virtual laboratory to train students' critical thinking skills. The purpose of this study is to test the validity of LKS and students' critical thinking skills. This research development model uses Nieveen (2006) which consists of three stages, namely preliminary research, prototyping stage, and stage assessment. The instruments used in this study were validation sheets and tests of critical thinking skills. Respondents of this study were students of class XI MIPA 3 of SMA 4 Jember with a total of 36 students. Based on the results of expert validation analysis the percentage was 81.67% with a very valid category and user validation obtained a percentage of 95.31% with a very valid category. The results of the data analysis of each indicator the critical thinking ability suggests that the critical thinking ability of grade XI students in MIPA 3 belongs to good category. The conclusion of this study was that the development of worksheets based on a virtual laboratory assisted scientific approach can improve students' critical thinking skills. Key word : critical thinking skills, scientific approach, validation